Recent evidence on input subsidy programs in Africa: Highlights from a spcial issue of Agricultural Economics - International Food Policy Research Institute (International Food Policy Research Institute, 2013)
Input Subsidy Programs (ISPs) have made a big comeback in Africa. Introduced by donors in the early 1970s, ISPs were meant to help smallholder farmers invest in fertilizer and improved seed varieties, overcome limited access to input markets, and ultimately increase crop production. The programs were poorly managed, however, and were largely eliminated in the 1980s and early 1990s under structural adjustment programs. They resurfaced in the mid-2000s and on a much grander scale.